Reverse Phase HPLC Analysis of Atomoxetine in Pharmaceutical Dosage Forms - Jagadeesh, B.V.V.S.; Satyanarayana Raju, S.; Jayathirtha Rao, V.; Seshagiri Rao, J.V.L.N. (Asian Journal of Chemistry, 2010)
A high performance liquid chromatographic method has been proposed for the determination of atomoxetine HCl in pure and dosage forms. The drug was chromatographed on a C-18 column using a mixture of water (containing 0.2 % of triethyl amine) and acetonitrile in the ratio of 15:85 v/v as the mobile phase at a flow rate of 1.0 mL/min. Pioglitazone was used as an internal standard and the detection was done at 270 nm. Linearity was observed in the concentration range of 10-200 μg/mL. The intra and inter-day variation was found to be less than 1 % showing high precision of the assay method. The mean per cent recovery of the drug from a sample solution containing 100 μg/mL was 99.40 ± 0.46 indicating high accuracy of the proposed method. Due to its simplicity, rapidness, high precision and accuracy the proposed method may be used for determining atomoxetine HCl in pure drug samples and dosage forms.